2021
DOI: 10.1038/s41467-021-21045-2
|View full text |Cite
|
Sign up to set email alerts
|

CD39+PD-1+CD8+ T cells mediate metastatic dormancy in breast cancer

Abstract: Some breast tumors metastasize aggressively whereas others remain dormant for years. The mechanism governing metastatic dormancy remains largely unknown. Through high-parametric single-cell mapping in mice, we identify a discrete population of CD39+PD-1+CD8+ T cells in primary tumors and in dormant metastasis, which is hardly found in aggressively metastasizing tumors. Using blocking antibodies, we find that dormancy depends on TNFα and IFNγ. Immunotherapy reduces the number of dormant cancer cells in the lung… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 78 publications
(14 reference statements)
1
36
0
Order By: Relevance
“…Nevertheless, the association of CD127− CD39 hi , but not of CD127+ CD39 lo Trm cells with improved OS and BC-specific survival in the METABRIC cohort, their increase presence at the tumor site compared to adjacent tissue and the peripheral blood, and in metastatic vs. nonmetastatic lymph nodes suggests that CD39 is a marker of bona fide tumor-reactive T cells also in BC. In line with this conclusion, a study recently published while this paper was under review mechanistically linked the infiltration of CD39 hi PD-1 hi T cells to metastatic dormancy in BC 38 . Collectively, these results thus extend a previous study in BC patients on the prognostic role of CD8+ CD103+ Trm cells as a whole 12 and pinpoint those T cells that are preferentially associated with delayed tumor growth with enhanced precision.…”
Section: Discussionsupporting
confidence: 68%
“…Nevertheless, the association of CD127− CD39 hi , but not of CD127+ CD39 lo Trm cells with improved OS and BC-specific survival in the METABRIC cohort, their increase presence at the tumor site compared to adjacent tissue and the peripheral blood, and in metastatic vs. nonmetastatic lymph nodes suggests that CD39 is a marker of bona fide tumor-reactive T cells also in BC. In line with this conclusion, a study recently published while this paper was under review mechanistically linked the infiltration of CD39 hi PD-1 hi T cells to metastatic dormancy in BC 38 . Collectively, these results thus extend a previous study in BC patients on the prognostic role of CD8+ CD103+ Trm cells as a whole 12 and pinpoint those T cells that are preferentially associated with delayed tumor growth with enhanced precision.…”
Section: Discussionsupporting
confidence: 68%
“…A discrete population of CD39+PD-1+CD8+ T cells mediates metastatic dormancy in breast cancer. These distinct cells are only found in primary tumors and in dormant metastasis, but they are hardly found in aggressively metastasizing tumors [ 38 ].…”
Section: Dormancy Nichementioning
confidence: 99%
“…Extending our knowledge of immune cell subpopulations, their functional states, and the roles that these cells play in dormancy, recurrence, and treatment susceptibility of ER+ metastatic disease in different locations, is a critical area of need. A recent study suggested the intriguing possibility that a T cell subset may mediate tumor dormancy [112].…”
Section: Differences Between the Microenvironments Of Primary And Metastatic Er+ Tumorsmentioning
confidence: 99%